Cost-effectiveness of augmenting universal hepatitis B vaccination with immunoglobulin treatment: a case study in Zhejiang Province, East China - Zeng, Yanbing (Hum Vaccin Immunother, 2019)
Objective: To evaluate the cost-effectiveness of the current strategy combining universal vaccination with hepatitis B immunoglobulin (HBIG) treatment for infants of hepatitis B surface antigen (HBsAg) positive mothers compared with universal vaccination with hepatitis B vaccine only. Methods: A decision tree model with a Markov process was constructed and used to simulate the lifetime of the birth cohort in Zhejiang Province during 2016. The current strategy was compared against universal vaccination with respect to costs and health effects. Costs were assessed from the health care system perspective. Health effects were measured by the number of hepatitis B virus (HBV) related diseases and deaths avoided and quality-adjusted life-years (QALYs) gained. The incremental cost‑effectiveness ratio (ICER) is calculated and compared to standard willingness-to-pay thresholds. A one-way sensitivity analysis and a probabilistic sensitivity analysis (PSA) were performed to assess parameter uncertainties. Results: Over the cohort’s lifetime, 182 acute symptomatic infections, 2215 chronic infections, 872 cases of cirrhosis, 595 cases of hepatocellular carcinoma (HCC) and 1,350 HBV-related deaths among the cohort of 624,000 infants would be further avoided by the current strategy compared to universal vaccination. Universal vaccination was dominated by the current strategy that produced not only higher total QALYs, but also had lower costs. The results remained robust over a wide range of assumptions. Conclusions: The current strategy was cost saving compared to universal vaccination, and continuing the current strategy is recommended to further decrease the burden of hepatitis B.